THE EFFECT OF INDUCTIVE LEARNING MODEL ON LEARNING RESULT OF CLASS XI SEMESTER I SMK - Dilla Pratama; Abdul Hakim (Universitas Negeri Medan, 2018)
This study aimed to determine the effect of using Inductive learning model on student learning outcomes on static fluid materials class XI Semester I SMK Private Taman Siswa Binjai T.P 2017/2018. This type of research is quasi experiment using two group pretest posttest design. The population in this study is all students of class XI SMK Private Taman Siswa Binjai. Sampling was done by cluster random sampling technique consisting of two classes, namely experimental class applied Inductive learning model, and control class applied conventional learning. The instrument used in this study is the test of learning outcomes in the form of multiple choice. The result showed that the average of pretest of experiment class was 31,99 and control class was 26,77 while experiment class average was 76,39 and control class was 67,57. The result of t test is obtained tcount> ttable (3.52> 1.99) so it can be concluded that there is influence of the use of Inductive learning model to student learning result on static fluid material class XI SMK Private Taman Siswa Binjai T.P 2017/2018